2014
DOI: 10.3389/fnhum.2014.00949
|View full text |Cite
|
Sign up to set email alerts
|

Auditory-motor entrainment and phonological skills: precise auditory timing hypothesis (PATH)

Abstract: Phonological skills are enhanced by music training, but the mechanisms enabling this cross-domain enhancement remain unknown. To explain this cross-domain transfer, we propose a precise auditory timing hypothesis (PATH) whereby entrainment practice is the core mechanism underlying enhanced phonological abilities in musicians. Both rhythmic synchronization and language skills such as consonant discrimination, detection of word and phrase boundaries, and conversational turn-taking rely on the perception of extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
115
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 104 publications
7
115
1
1
Order By: Relevance
“…The significant gains in reading accuracy and reading comprehension for the intervention group confirmed previous findings showing that a rhythm-based intervention significantly improved the reading accuracy and comprehension of poor readers (Long 2014;Long and Hallam, 2012) and findings demonstrating that the ability to synchronize with a beat is positively correlated with better pre-reading skills (Carr et al, 2014;Tierney and Kraus, 2014;Kraus and Slater, 2016), better cognitive and linguistic skills (Tierney and Kraus, 2013b).…”
Section: Discussionsupporting
confidence: 83%
“…The significant gains in reading accuracy and reading comprehension for the intervention group confirmed previous findings showing that a rhythm-based intervention significantly improved the reading accuracy and comprehension of poor readers (Long 2014;Long and Hallam, 2012) and findings demonstrating that the ability to synchronize with a beat is positively correlated with better pre-reading skills (Carr et al, 2014;Tierney and Kraus, 2014;Kraus and Slater, 2016), better cognitive and linguistic skills (Tierney and Kraus, 2013b).…”
Section: Discussionsupporting
confidence: 83%
“…Perceptual-motor synchronization ability has been linked to phonological skills (85)(86)(87), suggesting that synchronization and the knowledge of speech sounds rely on shared neural resources. One possibility is that both phonological awareness and auditory-motor synchronization draw on the ability to precisely track sound event timing (88). Given that both music training and JROTC training enhance phonological awareness and involve synchronization with perceptual cues, future work comparing music training to a passive control group could reveal a divergence not reported here.…”
Section: Discussionmentioning
confidence: 80%
“…The causal link between poor temporal processing and dyslexia has been recently supported by the results of an intervention study, which showed that music training based on rhythm has strong beneficial effects on phonological awareness and reading in severely impaired dyslexic children (Flaugnacco et al., ). As an explanation for this cross‐domain transfer between music and reading, the authors refer to the precise auditory timing hypothesis (PATH) (Tierney & Kraus, ). According to this hypothesis, the enhanced phonological abilities in musically trained children are related to the high degree of precision in audio‐motor timing required by music, possibly leading to an enhanced perception of the timing of speech sounds.…”
Section: Discussionmentioning
confidence: 99%